Improving the Power Electronics Laboratory teaching/learning process: an interactive web tool - Trujillo-Aguilera, Davinia; Sotorrío-Ruiz, Pedro Juan; Blázquez-Parra, Elidia Beatriz (My University, 2017)
European Higher Education Area; Power Electronics Laboratory; educational methods Resumen: The forthcoming European Higher Education Area implies an important change in the teaching/learning process: it is necessary to get students more involved as well as to promote their independence and active participation. To achieve this objective, the new teaching methodologies aimed at more effective and appropriate learning for professional practice involve the use of audiovisual, computer and multimedia tools on the part of lecturers. Therefore, a web tool, based on a content management system, has been developed for the teaching in Power Electronics Laboratory. Moreover, the use of these multimedia tools makes possible to promote the students independence. Finally, the use of this web tool results in a very significant increase in the motivation students.
Keywords: Tecnología - Estudio y enseñanza - Innovaciones tecnológicas; Teaching-learning process; European Higher Education Area; Power electronics laboratory; Educational methods